2017
DOI: 10.1007/s11187-017-9951-x
|View full text |Cite
|
Sign up to set email alerts
|

Does mobile money use increase firms’ investment? Evidence from Enterprise Surveys in Kenya, Uganda, and Tanzania

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 33 publications
6
67
0
1
Order By: Relevance
“…By 2011, the M‐Pesa system in Kenya alone handled more transactions than Western Union did globally (Kendall et al , p. 3). Mobile money now plays an essential role in virtually every sector of the Kenyan economy (Islam et al ). Ninety‐five per cent of small businesses reported that they readily accept mobile money in exchange for goods and service and to pay their workers (Gikenye ).…”
Section: The Kenyan Model: the Enabling Approach Applied To M‐pesamentioning
confidence: 99%
“…By 2011, the M‐Pesa system in Kenya alone handled more transactions than Western Union did globally (Kendall et al , p. 3). Mobile money now plays an essential role in virtually every sector of the Kenyan economy (Islam et al ). Ninety‐five per cent of small businesses reported that they readily accept mobile money in exchange for goods and service and to pay their workers (Gikenye ).…”
Section: The Kenyan Model: the Enabling Approach Applied To M‐pesamentioning
confidence: 99%
“…Suri and Jack (2016) find that access to mobile money lifted 2% of Kenyan households out of extreme poverty. Islam et al (2017) highlight a positive effect of firms' mobile money use on firm investment. This impact is related to reduced transactional costs, increased firms' liquidity, and increased ability to establish credit worthiness by using data generated by mobile financial services use.…”
Section: How Do Mobile Financial Services Impact the Shadow Economy?mentioning
confidence: 92%
“…However, achieving the outcomes is heavily dependent on the ability of the firm in question, on the specific sector and country context, and on the enabling environment and policy framework in place. Islam et al (2016) understood that private investment can be an important engine of economic growth in East African countries that are plagued with adverse economic conditions, despite recent growth rate. Against this backdrop, there has been substantial penetration of mobile money, moving beyond simple person-to-person exchanges towards adoption by private firms.…”
Section: Concept and Theory About Innovation And Technologymentioning
confidence: 99%